2004
DOI: 10.1111/j.1365-2265.2004.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord plasma concentrations of adiponectin and leptin in healthy term neonates: positive correlation with birthweight and neonatal adiposity

Abstract: High adiponectin levels are present in the cord blood. Cord plasma adiponectin and leptin levels are positively correlated with birthweight and adiposity. This suggests that adiponectin may be involved in regulating fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
130
7
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 30 publications
(55 reference statements)
23
130
7
10
Order By: Relevance
“…(9) found no significant correlation between adiponectin concentration and anthropometric parameters. Another study suggested a reverse correlation between PI and adiponectin concentration (11,25). Some studies have shown a positive correlation between adiponectin concentration and birth weight (8,12,14,(16)(17)(18)(19)(20), but few have failed to find a significant correlation (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…(9) found no significant correlation between adiponectin concentration and anthropometric parameters. Another study suggested a reverse correlation between PI and adiponectin concentration (11,25). Some studies have shown a positive correlation between adiponectin concentration and birth weight (8,12,14,(16)(17)(18)(19)(20), but few have failed to find a significant correlation (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent studies have shown that cord blood adiponectin concentrations are correlated positively with birth weight, suggesting that fetal adiponectin levels are likely to influence fetal growth. 8,10,27,28 MazakiTovi et al 29 have reported that the cord blood adiponectin concentration in the smaller neonate of discordant twins is lower than that in the larger counterpart. Our result showing that cord blood adiponectin concentrations were positively correlated with birth weight s.d.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
“…Furthermore, we confirmed previous findings of no gender difference in adiponectin levels. 8,10,11,28 Serum adiponectin levels are known to be inversely correlated with body fat mass in adolescents and adults, whereas cord blood adiponectin concentrations are positively correlated with birth weight s.d. score, mostly determined by fat mass.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating leptin levels correlate with fat mass in adults and children [11]. Leptin is detectable in cord blood from the second trimester of intrauterine life and correlates with adiposity at birth [12]. Interestingly, serum leptin concentration correlates with body mass index (BMI) in infants [13].…”
Section: Introductionmentioning
confidence: 99%